Survival and Long-Term Cause-Specific Mortality Associated With Stage IA Lung Adenocarcinoma After Wedge Resection vs. Segmentectomy: A Population-Based Propensity Score Matching and Competing Risk Analysis - Zhao, Mengnan; Lu, Tao; Huang, Yiwei; Yin, Jiacheng; Jiang, Tian; Li, Ming; Yang, Xinyu; Zhan, Cheng; Feng, Mingxiang; Wang, Qun (Frontiers in Oncology, 2019)
Background: Limited resection has been carried out increasingly in early stage NSCLC as an alternative to standard lobectomy. This study aimed to investigate the differences in survival and long-term cause-specific mortality between wedge resec-tion and segmentectomy for treatment of stage IA lung adenocarcinoma. Method: Cases with primary lung adenocarcinoma that received wedge resection and segmentectomy between 2004 and 2015 were selected from the Surveillance, Epidemiology, and End Results (SEER) database. Propensity score matching was performed to balance the baseline covariates. Long-term cause-specific mortality was investigated through competing risk analysis. The overall survival (OS) was es-timated with the Kaplan-Meier method with the log-rank test. Univariate and multi-variate Cox proportional hazards regression analyses were performed to identify the independent prognostic factors. Results: Of the 3,046 cases included, 2,360 and 686 cases underwent wedge resec-tion and segmentectomy, respectively. After propensity score matching, 686 pairs were selected. Segmentectomy was associated with a significantly better OS in stage IA2, grade I/II, female, and married patients. The segmentectomy group had a higher lung-cancer specific mortality in 65–74 years of age, stage IA1 and IA3, male, and married patients, and a lower chronic obstructive pulmonary disease (COPD) spe-cific mortality in ≤64 and 65–74 years of age, stage IA1, IA2, and IA3, all grade, male, and married patients. The cardiovascular disease (CVD) specific mortality was also lower in the segmentectomy group in ≥75 years of age, stage IA1 and IA3, and grade I/II patients. Conclusion: Wedge resection was inferior to segmentectomy in terms of OS re-garding all included parameters. In most cases, the segmentectomy group had higher lung-cancer specific mortality and lower COPD and CVD specific mortality. Keywords: limited resection, lung adenocarcinoma, propensity score matching, competing risk analysis, SEER database.